Lobbying and the media : working with politicians and journalists - Burrell, Michael (Thorogood professional insights., 2001)
Annotation Lobbying is an art form, rather than a science, so there is inevitably an element of judgement in what line to take. The best lobbying is always based on accurate, up-to-date information and on a well-argued case, founded on credible evidence, and delivered to the right audiences in the right tone of voice at the right time. Sounds simple, but it isn't. This new Special Report shows you how.